If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k(7k + 5) = 0 Reorder the terms: 4k(5 + 7k) = 0 (5 * 4k + 7k * 4k) = 0 (20k + 28k2) = 0 Solving 20k + 28k2 = 0 Solving for variable 'k'. Factor out the Greatest Common Factor (GCF), '4k'. 4k(5 + 7k) = 0 Ignore the factor 4.Subproblem 1
Set the factor 'k' equal to zero and attempt to solve: Simplifying k = 0 Solving k = 0 Move all terms containing k to the left, all other terms to the right. Simplifying k = 0Subproblem 2
Set the factor '(5 + 7k)' equal to zero and attempt to solve: Simplifying 5 + 7k = 0 Solving 5 + 7k = 0 Move all terms containing k to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 7k = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 7k = 0 + -5 7k = 0 + -5 Combine like terms: 0 + -5 = -5 7k = -5 Divide each side by '7'. k = -0.7142857143 Simplifying k = -0.7142857143Solution
k = {0, -0.7142857143}
| 12b^2-8=6b | | X+(-4)=-7 | | -10+2x=3x-1+8x | | 12b^2-8=ab | | x^2(x+7)=40x+100 | | (y^2)-23y+130=0 | | 7n+20=6 | | 200-6x=500-6x | | 4n+3+20=6 | | -16t^2+5t+92=0 | | Y+-3=8 | | 0=9x+25+5y | | 2.5x+1.2-4=3.5 | | 4-4b+3b=-3-5b+5b | | 9+x+x=29 | | -6x^2-5x+7=0 | | (6x+4)-(9x-4)= | | 12n-7=-2 | | 2(x-1)-5= | | 8y-12x=0 | | 11.70=2.10+0.80x | | 2x^2-150=650 | | -100=2(-8-6r) | | 19=x^2-17 | | (2x^2-7xy+6y^2)= | | 11(2-2x)+4= | | 7(2k+3)= | | 20-x^2=-80 | | (y^2)-23y+112=0 | | b^2-4b=30+3b | | 2n+5=-13 | | -4.5x+1.4=-25.6 |